A comparison of running performance of elite female rugby union players using a global navigation satellite system - Yamamoto, H.; Iwata, S.; Takemura, M.; Tachibana, M.; Tsujita, J.; Hojo, T. (International Journal of Sport & Health Science, 2024)
This study aimed to clarify the physical demands on female rugby union players in Japan by analyzing the running performance of female rugby union players during matches and comparing those players or male rugby union players. Elite male and female rugby union players wore a Global Navigation Satellite System device with an integrated three-axis accelerometer during official matches to measure the total distance, distances traveled by different speed zones, and maximum speed. Physical demands of the variables per match were determined based on the data from the female rugby union players. Comparisons between female and male rugby union players showed that the high-speed running distance (p<0.01) and maximum speed (p<0.01) were significantly lower in the female rugby union players. At the same time, no significant differences were noted in the total distance. The data showed that the female rugby union players had a comparable but the lower high speed running performance during a match compared to male players, suggesting the importance of training focusing on increasing intensity for improving performance.